Src Mutation Induces Acquired Lapatinib Resistance in ERBB2-Amplified Human Gastroesophageal Adenocarcinoma Models - Hong, Yong Sang; Kim, Jihun; Pectasides, Eirini; Fox, Cameron; Hong, Seung-Woo; Ma, Qiuping; Wong, Gabrielle S.; Peng, Shouyong; Stachler, Matthew D.; Thorner, Aaron R.; Van Hummelen, Paul; Bass, Adam J. (PloS one, 2014)
ERBB2-directed therapy is now a routine component of therapy for ERBB2-amplified metastatic gastroesophageal adenocarcinomas. However, there is little knowledge of the mechanisms by which these tumors develop acquired resistance to ERBB2 inhibition. To investigate this question we sought to characterize cell line models of ERBB2-amplified gastroesophageal adenocarcinoma with acquired resistance to ERBB2 inhibition. We generated lapatinib-resistant (LR) subclones from an initially lapatinib-sensitive ERBB2-amplified esophageal adenocarcinoma cell line, OE19. We subsequently performed genomic characterization and functional analyses of resistant subclones with acquired lapatinib resistance. We identified a novel, acquired SrcE527K mutation in a subset of LR OE19 subclones. Cells with this mutant allele harbour increased Src phosphorylation. Genetic and pharmacologic inhibition of Src resensitized these subclones to lapatinib. Biochemically, Src mutations could activate both the phosphatidylinositol 3-kinase and mitogen activated protein kinase pathways in the lapatinib-treated LR OE19 cells. Ectopic expression of SrcE527K mutation also was sufficient to induce lapatinib resistance in drug-naïve cells. These results indicate that pathologic activation of Src is a potential mechanism of acquired resistance to ERBB2 inhibition in ERBB2-amplified gastroesophageal cancer. Although Src mutation has not been described in primary tumor samples, we propose that the Src hyperactivation should be investigated in the settings of acquired resistance to ERBB2 inhibition in esophageal and gastric adenocarcinoma.